Pharmacodynamic Profiling of Amoxicillin: Targeting Multidrug-Resistant Gram-Positive Pathogens Staphylococcus aureus and Staphylococcus pseudintermedius in Canine Clinical Isolates - Syed Al Jawad Sayem; Ga-Yeong Lee; Muhammad Aleem Abbas; Seung-Chun Park; Seung-Jin Lee (Antibiotics)
The rising threat of antimicrobial resistance (AMR) is a global concern in both human and veterinary medicine, with multidrug-resistant (MDR) pathogens such as Staphylococcus aureus and Staphylococcus pseudintermedius presenting significant challenges. Background/Objectives: This study evaluates the effectiveness of amoxicillin against these MDR pathogens in canine isolates using pharmacokinetic and pharmacodynamic parameters. Methods: Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and mutation prevention concentration (MPC) were assessed. Additionally, time-kill assays and post-antibiotic effect (PAE) assessments were performed. Epidemiological cutoff (ECOFF) values were established for both species to guide therapy. Results: S. aureus had a higher resistance rate (35.89%) than S. pseudintermedius (15.27%), with MIC50 values of 0.50 μg/mL and 0.25 μg/mL, respectively. The MPC analysis revealed that S. pseudintermedius required higher antibiotic concentrations (16.11 μg/mL) to prevent mutations compared to S. aureus (2.20 μg/mL). Time-kill assays indicated that higher amoxicillin dosages caused faster bacterial reduction. The PAE analysis showed extended post-treatment bacterial suppression at elevated doses, particularly against S. aureus. Conclusions: Species-specific amoxicillin dosing strategies are necessary due to differing resistance and susceptibility profiles between S. aureus and S. pseudintermedius. High-dose amoxicillin therapy is recommended to achieve optimal therapeutic outcomes for resistant SA, while slightly adjusted dosing can manage S. pseudintermedius infections. These findings provide essential insights for veterinary antimicrobial stewardship, underscoring the need for tailored therapeutic approaches to minimize AMR development while ensuring effective infection control.